Immunity and survival response of Atta cephalotes (Hymenoptera: Myrmicinae) workers to Metarhizium anisopliae infection: Potential role of their associated microbiota - Valencia-Giraldo, Sandra Milena; Niño-Castro, Andrea; López-Peña, Andrea; Trejos-Vidal, Danna; Correa-Bueno, Odair [UNESP]; Montoya-Lerma, James (Public Library of Science (PLoS), 2021)
Leaf-cutting ants of the genera Atta and Acromyrmex are at constant risk of epizootics due to their dense living conditions and frequent social interactions between genetically related individuals. To help mitigate the risk of epizootics, these ants display individual and collective immune responses, including associations with symbiotic bacteria that can enhance their resistance to pathogenic infections. For example, Acromyrmex spp. harbor actinobacteria that control infection by Escovopsis in their fungal gardens. Although Atta spp. do not maintain symbiosis with protective actinobacteria, the evidence suggests that these insects are colonized by bacterial microbiota that may play a role in their defense against pathogens. The potential role of the bacterial microbiome of Atta workers in enhancing host immunity remains unexplored. We evaluated multiple parameters of the individual immunity of Atta cephalotes (Linnaeus, 1758) workers, including hemocyte count, encapsulation response, and the antimicrobial activity of the hemolymph in the presence or absence of bacterial microbiota. Experiments were performed on ants reared under standard conditions as well as on ants previously exposed to the entomopathogenic fungus Metharrizium anisopliae. Furthermore, the effects of the presence/absence of bacteria on the survival of workers exposed to M. anisopliae were evaluated. The bacterial microbiota associated with A. cephalotes workers does not modulate the number of hemocytes under control conditions or under conditions of exposure to the fungal pathogen. In addition, infection by M. anisopliae, but not microbiota, increases the encapsulation response. Similarly, the exposure of workers to this fungus led to increased hemolymph antimicrobial activity. Conversely, the removal of bacterial microbiota did not have a significant impact on the survival of workers with M. anisopliae. Our results suggest that the bacterial microbiota associated with the cuticle of A. cephalotes workers does not play a role as a modulator of innate immunity, either at baseline or after exposure to the entomopathogen M. anisopliae. Further, upon infection, workers rely on mechanisms of humoral immunity to respond to this threat. Overall, our findings indicate that the bacterial microbiota associated with A. cephalotes workers does not play a defensive role.